Elastic optical networks : fundamentals, design, control, and management - Chatterjee, Bijoy Chand; Oki, Eiji, 1969- (Boca Raton, FL : CRC Press, 2020)
The rapid growth in communications and internet has changed our way of life, and our requirement for communication bandwidth. Optical networks can enable us to meet the continued demands for this bandwidth, although conventional optical networks struggle in achieving this, due to the limitation of the electrical bandwidth barrier. Flexgrid technology is a promising solution for future high-speed network design. To promote an efficient and scalable implementation of elastic optical technology in the telecommunications infrastructure, many challenging issues related to routing and spectrum allocation (RSA), resource utilization, fault management and quality of service provisioning must be addressed. This book reviews the development of elastic optical networks (EONs), and addresses RSA problems with spectrum fragment issues, which degrade the quality of service provisioning. The book starts with a brief introduction to optical fiber transmission system, and then provides an overview of the wavelength division multiplexing (WDM), and WDM optical networks. It discusses the limitations of conventional WDM optical networks, and discusses how EONs overcome these limitations. It presents the architecture of the EONs and its operation principle. To complete the discussion of network architecture, this book focuses on the different node architectures, and compares their performance in terms of scalability and flexibility. It reviews and classifies different RSA approaches, including their pros and cons. It focuses on different aspects related to RSA. The spectrum fragmentation is a serious issue in EONs, which needs to be managed. The book explains the fragmentation problem in EONs, discusses, and analyzes the major conventional spectrum allocation policies in terms of the fragmentation effect in a network. The taxonomies of the fragmentation management approaches are presented along with different node architectures. State-of-the-art fragmentation management approaches are looked at. A useful feature of this book is that it provides mathematical modeling and analyzes theoretical computational complexity for different problems in elastic optical networks. Finally, this book addresses the research challenges and open issues in EONs and provides future directions for future research.
Preface. Introduction to optical networks. Elastic optical networks. Network and node architectures for elastic optical networks. Routing and spectrum allocation for elastic optical networks. Different aspects related to routing and spectrum allocation. Spectrum fragmentation problems in elastic optical networks. Spectrum fragmentation management approaches considering non defragmentation. Spectrum fragmentation management approaches considering defragmentation. Spectrum fragmentation management approaches in 1+1 protected elastic optical networks. Spectrum fragmentation management in software-defined elastic optical networks. Mathematical modeling for problems in elastic optical networks. Computational complexity analysis for problems in elastic optical networks. Research issues and challenges in elastic optical networks. References. Index.
OCLC-licensed vendor bibliographic record.
Keywords: Optical fiber communication; SCIENCE / Life Sciences / General; TECHNOLOGY / Lasers